2011
DOI: 10.1111/j.1349-7006.2011.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel activity of acriflavine against colorectal cancer tumor cells

Abstract: A high-throughput screen of the cytotoxic activity of 2000 molecules from a commercial library in three human colon cancer cell lines and two normal cell types identified the acridine acriflavin to be a colorectal cancer (CRC) active drug. Acriflavine was active in cell spheroids, indicating good drug penetration and activity against hypoxic cells. In a validation step based on primary cultures of patient tumor cells, acriflavine was found to be more active against CRC than ovarian cancer and chronic lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 34 publications
3
48
0
2
Order By: Relevance
“…Administration of other chemotherapy drugs in combination with 5-FU is reported to improve the response rate of patients (9,11). In the present study, the effect of ACF on the anticancer activity (19) demonstrated that ACF has a cytotoxic effect in monolayer and multicellular spheroid culture of CRC cells, and their results demonstrated that ACF has a good cellular penetration and cytotoxic activity against hypoxic CRC cells.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Administration of other chemotherapy drugs in combination with 5-FU is reported to improve the response rate of patients (9,11). In the present study, the effect of ACF on the anticancer activity (19) demonstrated that ACF has a cytotoxic effect in monolayer and multicellular spheroid culture of CRC cells, and their results demonstrated that ACF has a good cellular penetration and cytotoxic activity against hypoxic CRC cells.…”
Section: Discussionsupporting
confidence: 57%
“…It appears that pretreatment with ACF predisposes CRC cells to the cytotoxic effect of the main drug, i.e. 5-FU, through the inhibition of HIF-1α and topoisomerase 2 activity as suggested previously (17,19). However, the exact molecular mechanism of ACF cytotoxicity against CRC cells remains to be elucidated (19).…”
Section: Ic 50 Value µM --------------------------------------------mentioning
confidence: 79%
See 1 more Smart Citation
“…Several studies have indicated that acridines possess properties that inhibit tumor growth and cancer cell proliferation (21)(22)(23)(24). Acriflavine, an acridine derivative has previously been used as an imaging contrast agent due to the ability to pass through the cell membrane and strongly label acidic constituents (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, this observation period does not exclude potential carcinogenic effects at later time points. Finally, acriflavine showed anticancer activity in vitro in recently published studies [18,19]. Thus, acriflavine might be an interesting substance for various diagnostic and therapeutic purposes in humans.…”
Section: Staining Agentmentioning
confidence: 99%